Creación de masa madre a base de máchica y su aplicación en la panificación - Varela Jaramillo, Mauricio José (2024)
Machica, a traditional Andean flour made from roasted and milled barley, is underutilized in the baking sector, despite its nutritional properties. Historically consumed in Latacunga, Ecuador, its use is mainly limited to traditional drinks and soups, ignoring its potential in baking, especially in the creation of sourdough. This integrative project focused on exploring the application of machica flour in the elaboration of sourdough and its subsequent use in bread making, aligning with Sustainable Development Goal number two, 'zero hunger', which seeks to ensure healthy and nutritious food for all. The general objective was to elaborate machica based sourdough for its application in artisanal baking. The specific objectives included: to conduct bibliographic research on the nutritional properties of machica, to determine types of bread compatible with this sourdough, and to make three types of bread by hand to evaluate the viability of the product. The methodology combined bibliographic, inductive and experimental studies. The fermentation properties of machica were analyzed, compatible breads were identified and experimental tests were conducted to adjust recipes. The results demonstrated that machica sourdough is viable and nutritious, and its application in artisanal baking can diversify the supply of products in the Ecuadorian market. In conclusion, the project not only highlighted the nutritional value of machica, but also promoted its use in baking.